Fast analytical techniques for electrical and electronic circuits - Vorpérian, Vatché, 1952- (Cambridge University Press, 2002)
In this unique book, Vorpérian describes a remarkable alternative to nodal or loop analysis for analysing linear circuits. This technique can be used to solve, almost by inspection, complex circuits in symbolic form and obtain meaningful analytical answers for any transfer function or impedance.
Keywords: Electronic circuits.; Electric circuits.; Electric circuit analysis.; elektronické knihy; electronic books